Genetic parameters estimated at receiving for circulating cortisol, immunoglobulin G, interleukin 8, and incidence of bovine respiratory disease in feedlot beef steers - Cockrum, R. R.; Speidel, S. E.; Salak-Johnson, J. L.; Chase, C. C. L.; Peel, R. K.; Weaber, Robert L.; Loneagan, G. H.; Wagner, J. J.; Boddhireddy, P.; Thomas, M. G.; Prayaga, K.; Denise, S.; et al. (My University, 2017)
Bovine respiratory disease complex (i.e., shipping fever and bacterial bronchopneumonia) is a multifaceted respiratory illness influenced by numerous environmental factors and microorganisms. Bovine respiratory disease (BRD) is just one component of BRD complex. Because BRD is moderately heritable, it may be possible to reduce the incidence of BRD through genetic selection. The objectives of this study were to determine the heritability and associative genetic relationships among immune system traits (i.e., cortisol, total IgG, IgG isotypes, and IL-8) in cattle monitored for BRD incidence. At an average of 83 d after weaning (219 d age and mean = 221.7 kg [SD 4.34]), crossbred Bos taurus steer calves (n = 2,869) were received at a commercial feedlot in southeastern Colorado over a 2-yr period. At receiving, jugular blood samples were collected at 212 (yr 1) and 226 d (yr 2) of age for immune trait analyses. The BRD phenotype was defined as a binomial variable (0 = no and 1 = yes) and compared with immune system traits measured at receiving (prior to illness onset). An animal identified as BRD positive exhibited ? 2 clinical signs (i.e., eye or nasal discharge, cough, lethargy, rapid breathing, acute interstitial pneumonia, or acute upper respiratory syndrome and/or a rectal temperature > 39.7°C). Heritability and genetic correlation estimates for categorical variable BRD, cortisol, IgG, IgG1, IgG2, and IL-8 were estimated from a sire model using ASREML. Heritability estimates were low to moderate for BRD (0.17 ± 0.08), cortisol (0.13 ± 0.05), IgG (0.15 ± 0.05), IgG1 (0.11 ± 0.05), IgG2 (0.24 ± 0.06), and IL-8 (0.30 ± 0.06). A moderate negative genetic correlation was determined between BRD and cortisol (rg = ?0.19 ± 0.32). Moderate positive correlations were found between BRD with IgG (0.42 ± 0.28), IgG1 (0.36 ± 0.32), and IL-8 (rg = 0.26 ± 0.26). Variation in the BRD phenotype and immune system traits suggested herd health improvement may be achieved through genetic selection. © 2016 American Society of Animal Science. All rights reserved.
Citation: Cockrum, R. R., Speidel, S. E., Salak-Johnson, J. L., Chase, C. C. L., Peel, R. K., Weaber, R. L., . . . Enns, R. M. (2016). Genetic parameters estimated at receiving for circulating cortisol, immunoglobulin G, interleukin 8, and incidence of bovine respiratory disease in feedlot beef steers. Journal of Animal Science, 94(7), 2770-2778. doi:10.2527/jas2015-0222
Keywords: Bovine Respiratory Disease; Cattle; Immune System